Duodenal adenocarcinoma: more questions than answers - Dave, Apeksha; Wiseman, Jason T.; Cloyd, Jordan M. (Laparoscopic Surgery, 2018)
Duodenal adenocarcinoma (DA) is an aggressive malignancy. It represents the most common adenocarcinoma of the small intestine, with the majority arising in segment D2 (1-3). The incidence of DA however is rare; it represents less than 1% of all gastrointestinal cancers (4-6). DA usually presents with vague symptoms and can be difficult to diagnose until a patient develops gastrointestinal bleeding or obstruction which frequently results in delays of diagnosis (7). These factors influence the lack of high-quality evidence on outcomes for those with DA, relative scarcity of definitive treatment recommendations, and resulting overall modest prognosis.